2018
DOI: 10.1093/scan/nsy077
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control and network disruption in remitted depression: a correlate of childhood adversity

Abstract: Individuals in a major depressive episode often display impairment in cognitive control, and this impairment exists outside of the acute phase of illness. Impairment in cognitive control also has been associated with exposure to childhood adversity (CA). The current study examined whether exposure to CA can explain variance in a component of cognitive control—inhibitory control—independent of diagnostic status in young adults with and without a history of depression. Healthy control individuals (n = 40) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 70 publications
4
19
1
Order By: Relevance
“…In this study, we found that DVH was associated with significantly lower ReHo value in the right middle frontal gyrus, and thus can speculate that DVH may give rise to the dysfunction of the middle frontal gyrus. Moreover, we found that DS showed a negative correlation with the mean ReHo signal value of the right middle frontal gyrus ( r = -0.6239, P = 0.0001), which was consistent with the findings of Quinn et al [ 32 ]. Therefore, our study suggested that DVH has a harmful influence on the right middle frontal gyrus, which might be related to depression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that DVH was associated with significantly lower ReHo value in the right middle frontal gyrus, and thus can speculate that DVH may give rise to the dysfunction of the middle frontal gyrus. Moreover, we found that DS showed a negative correlation with the mean ReHo signal value of the right middle frontal gyrus ( r = -0.6239, P = 0.0001), which was consistent with the findings of Quinn et al [ 32 ]. Therefore, our study suggested that DVH has a harmful influence on the right middle frontal gyrus, which might be related to depression.…”
Section: Discussionsupporting
confidence: 92%
“…It plays a vital role in cognitive function and attention[ 31 ]. Quinn et al [ 32 ] found that dysfunction of the middle frontal gyrus was associated with depression. Our previous studies reported that the middle frontal gyrus is involved in monocular blindness and acute eye pain[ 7 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our investigation of the FC alterations across different phases of MDD support the view that MDD is a chronic disease characterized by progressive functional impairments. Previous studies have revealed that some prominent symptoms and aberrant FC shown in acute depressive episodes would remain even in the clinical remission phase 42 44 . And these residual symptoms and abnormalities might lead to functional impairment, recurrence and poor prognosis of MDD 4 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy, intellectual and cortical sensory deficits, and psychiatric manifestations are the most frequent manifestations of any mitochondrial disease (Andreazza et al, 2018;Finsterer, 2009;Gorman et al, 2016;Kim et al, 2019;Pei and Wallace, 2018;Reinhart and Nguyen, 2019;Srivastava et al, 2018;Sullivan et al, 2018;Nierenberg et al, 2018). Neural processes with high energy demand, such as neuronal maturation/development and plasticity, as well as impaired synaptic physiology and synchronous neuronal activity (Alves et al, 2014;Boku et al, 2018;Quinn et al, 2018;Reinhart and Nguyen, 2019;Serafini, 2012) could explain the proximal neuropsychological presentation in mitochondrial disease. To date, however, the lack of translational model systems of impaired brain bioenergetics has hampered our understanding of the exact nature of disease pathobiology and the development of disease-modifying therapies.…”
Section: Introductionmentioning
confidence: 99%